Geostatistical methods for reservoir geophysics - Azevedo, Leonardo; Soares, Amilcar (Springer, 2017)
This book presents a geostatistical framework for data integration into subsurface earth modeling. It provides geostatistical background information, including detailed descriptions of the main geostatistical tools traditionally used in earth related sciences to infer the spatial distribution of a given property of interest. This framework is then directly linked with applications in the oil and gas industry for simultaneous integration of geophysical data (e.g. seismic reflection data) and well-log data into reservoir modeling and characterization. All of the cutting-edge methodologies presented here are first approached from a theoretical point of view and then supplemented by sample applications from real case studies involving different geological scenarios and different challenges. The book offers a valuable resource for students who are interested in learning more about the fascinating world of geostatistics and reservoir modeling and characterization. It offers them a deeper understanding of the main geostatistical concepts and how geostatistics can be used to achieve better data integration and reservoir modeling.
Keywords: Petroleum -- Geology -- Statistical methods.; Petroleum -- Geology -- Mathematical models.; Prospecting -- Geophysical methods.; Gas reservoirs.; Oil industries -- Statistics.; Gas industry -- Statistics.; elektronické knihy; electronic books